2017
DOI: 10.1002/chem.201604816
|View full text |Cite
|
Sign up to set email alerts
|

Dual 5′ Cap Labeling Based on Regioselective RNA Methyltransferases and Bioorthogonal Reactions

Abstract: The ability to detect and localize defined RNA strands inside living cells requires probes with high specificity, sensitivity, and signal-to-background ratio. To track low-abundant biomolecules, such as strands of regular mRNA, and distinguish fluorescence signal from the background after bioorthogonal reactions in cells, it is imperative to employ turn-on concepts. Here, we have presented a straightforward enzymatic approach to allow site-specific modification of two different positions on the 5' cap of eukar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 68 publications
0
34
0
2
Order By: Relevance
“…184 By using the above-mentioned methyltransferases and exploring their regioselectivity, dual 5 0 Cap labelling of mRNAs was also achieved. 185 4.3.3 Enzyme-mediated modification of DNA. DNA IEDDA labelling has also been achieved using DNA polymerase, reverse transcriptase via primer extension (PEX) or reverse transcription.…”
Section: Alternative Enzymatic Methods or Enzyme Tags For Protein Modmentioning
confidence: 99%
“…184 By using the above-mentioned methyltransferases and exploring their regioselectivity, dual 5 0 Cap labelling of mRNAs was also achieved. 185 4.3.3 Enzyme-mediated modification of DNA. DNA IEDDA labelling has also been achieved using DNA polymerase, reverse transcriptase via primer extension (PEX) or reverse transcription.…”
Section: Alternative Enzymatic Methods or Enzyme Tags For Protein Modmentioning
confidence: 99%
“…At the same time, we found that hTgs1 did not accept any AdoMet analogues in previous studies . To this end, CMTR1 160–549 was incubated with the AdoMet analogues SeAdoYn or Hey‐SAM, synthetic RNA 8 equipped with a cap0, and MTAN (Figure S10) . Reaction progress was monitored by means of HPLC.…”
Section: Resultsmentioning
confidence: 83%
“…This is consistent with the in vitro results, showing that recombinant METTL3–METTL14 complex efficiently transfers the propargyl group to the N 6 -position in adenosine. Many other cellular MTases, including the ones from the eukaryotic 5′-capping machinery, also show a high level of promiscuity in vitro regarding the SAM analogues [ 47 ]. After the total RNA isolation, the transferred propargyl groups can be functionalized in a click-reaction with biotin azide, which enables enrichment of the RNA regions containing methylation sites on streptavidin beads.…”
Section: Approaches Involving Modification Steps In Vivo mentioning
confidence: 99%